The Effect of folkdance on the physical fitness of the first year students of the Divine Word College of Bangued - Barcena, Johnny C. (Vigan City, Ilocos Sur : [s.n.], 2005)
This study determined the effects of folkdance activities on the physical fitness of the first year students of the Divine Word College of Bangued (DWCB) during the second semester, SY 2004-2005 along abdominal strength, muscular endurance, cardiovascular, flexibility, and body mass index.
Bibliography: pages 44-46.
CHED-La Union
Keywords: Folk dancing; Physical fitness